La sociedad cooperativa europea domiciliada en España - Pastor Sempere, Carmen (REVESCO. Revista de Estudios Cooperativos, 2009)
With this paper we try to offer and explain the main problems and how they should be resolved, in order to establish an ECS (Europen Co-operative Society) in Spain.
Keywords: SCE; Companies domiciled in Spain; Aid State economic regime